Natural Grassland Vegetation Types for the Grassland Zoning in Relation to the Climate in Japan. (<Special Feature>Ecological Consideration for the Distribution of Natural Grassland Vegetation Zones in Relation to the Climate and Climate Change in Japan) - 西村, 格; 佐々木, 寛幸; 西村, 由紀 (日本草地学会, 2001)
application/pdf In order to predict the changes of the natural grassland vegetation in global warming, it is necessary for us to clarify the relationship between the natural grassland vegetation zones and the climate. But that relationship has not been argued out in Japan. Therefore we investigated which of the vegetation types are appropriate to clarify that relationship from the first. We concluded that the short-grass type vegetation established under the artiGcial and natUral pressures in the process of the grass-land succession was the most appropriate for the above purpose. As the results, we separated the temperate vegetation from the subarctic one with Zoysia japonica-type grassland. The cool-temperate vegetation was separated from the warm-temperate vegetation with the ranges of Sasa and Pleioblastus. Article journal article